Biological Characteristics, Impacts, and Management of Crenate Broomrape (Orobanche crenata) in Faba Bean (Vicia faba): A Review - Negewo, Takele; Ahmed, Seid; Tessema, Taye; Tana, Tamado (Frontiers in Agronomy, 2022)
Crenate broomrape, Orobanche crenata Forskal belongs to the family Orobanchaceae. It is a root holoparasitic weed devoid of chlorophyll and entirely dependent on host plants for its growth requirement. This parasite considerably infects plant species of the families Leguminosae, Apiaceae, and Asteraceae in highly infested drier and warmer areas of the world. It is well-known for its devastating effects on cool-season food legumes especially on faba bean (Vicia faba L.) and for threatening the livelihood of subsistence farmers. Yield losses of infected crops reach up to 100% depending on the level of infection by the parasitic weed. The long-term impact of the parasite is even more serious than its short-term effects as its numerous minute seeds are easily spread using different mechanisms and persist in the soil for up to 20 years. Besides, its management is difficult as no single method proved to be effective, economical, and complete in managing the weed. This review article gives an overview of information on the biological characteristics and harmful effects of crenate broomrape and summarizes scientifically proven management techniques for its effective management. Different approaches should be validated, demonstrated, and scaled for wider uses to manage crenate broomrape sustainably and boost the host crop productivity. Therefore, besides narrowing the knowledge gaps on the weed biology more strengthened efforts in searching for host plant resistance and/or tolerance based integrated management approaches by considering socio-economic and ecological conditions of faba bean growers are found paramount importance.